Perusahaan Modal Ventura Perspektif Ekonomi Syariah - Dewi Kumalasari (Universitas Islam Lamongan, 2016)
In Indonesia, so many financial institutions that provide financing, either in the form of equity or in the form of loan. Financial institutions that provide financing in the form of loan, such as financial institutions of Islamic banks, require borrower to provide collateral and require financing prospective customer to attach financial statement of the business operated. The problem arises when the company that is going to start a business wants to apply for a loan to the Islamic bank, which new company has no the financial statements at all, even has no collateral required by the Islamic bank. Financing is one of the important things for companies that are just about to start a business, but it is difficult to obtain. Are there financial institutions, particularly the Islamic financial institutions that provide loan without requiring collateral or attach the financial statements of the business? A new company which is just opening a business, and have difficulties in getting funding, but still want to obey sharia principles, the right solution is a Sharia venture capital. On the one hand, the presence of sharia venture capital not only merely accommodates the interest of Muslims, but also emphasises on factors of advantage and benefit by providing financing help for economic activities, both small, medium, and large enterprises with the principles of sharia compliance. Venture capital is a form of the provision of capital to a company in the form of capital which, in this case, the company does not require collateral, like in Islamic banking. The company that wants to borrow from financial institutions, but do not want to earn or pay interest, as in conventional bank, the sharia venture capital sharia is the solution. Furthermore, to introduce and expand the knowledge of venture capital, especially sharia venture capital, this paper will discuss in one paper entitled sharia venture capital perspective on sharia economics. Keywords: Sharia economics, venture capital